Economic problems of Latin America - Hunter, John M.; Foley, James William (Boston: Houghton Mifflin, 1975)
The book introduces readers to the economic problems of Latin America. Political, social and cultural, factors are discussed only as they relate to particular aspects of the economic problems analyzed. The book is written primarily for undergraduate students in the fields of economic development and Latin American studies.
Includes index.
Bibliography: p. 365-375.
rpm 13/06/2017
Loans
Keywords: Latin America -- Economic conditions -- 1918-1945.; Latin America Economic conditions; Economic history; Latin America